2019
DOI: 10.1039/c9dt03045j
|View full text |Cite
|
Sign up to set email alerts
|

A dipyrromethane-based diphosphane–germylene as precursor to tetrahedral copper(i) and T-shaped silver(i) and gold(i) PGeP pincer complexes

Abstract: A dipyrromethane-based PGeP germylene has allowed the synthesis of unusual tetrahedral copper(i) and T-shaped silver(i) and gold(i) germyl complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 78 publications
1
28
0
Order By: Relevance
“…Germylene XXX was prepared by treating GeCl 2 (diox) with the dilithiated form of the diphosphane (HpyrmP i Pr 2 ) 2 CMe 2 (Figure ), which was in turn synthesized in two steps from 5,5‐dimethyldipyrromethane, (HpyrH) 2 CMe 2 , by a synthetic method previously used to prepare other phosphane‐functionalized pyrroles and dipyrromethanes . Its XRD structure showed that the Ge atom is in a pyramidal arrangement attached to both pyrrolyl rings and to one phosphane group, but the compound is fluxional in solution, as it easily exchanges the pendant and the attached phosphane groups.…”
Section: Pgep Pincers With Bis(pyrrolyl)germylene and Dipyrromethamentioning
confidence: 99%
See 4 more Smart Citations
“…Germylene XXX was prepared by treating GeCl 2 (diox) with the dilithiated form of the diphosphane (HpyrmP i Pr 2 ) 2 CMe 2 (Figure ), which was in turn synthesized in two steps from 5,5‐dimethyldipyrromethane, (HpyrH) 2 CMe 2 , by a synthetic method previously used to prepare other phosphane‐functionalized pyrroles and dipyrromethanes . Its XRD structure showed that the Ge atom is in a pyramidal arrangement attached to both pyrrolyl rings and to one phosphane group, but the compound is fluxional in solution, as it easily exchanges the pendant and the attached phosphane groups.…”
Section: Pgep Pincers With Bis(pyrrolyl)germylene and Dipyrromethamentioning
confidence: 99%
“…Germylene XXX reacted readily with [Cu 4 (µ 3 ‐Cl) 4 (PPh 3 ) 4 ] (1:1/4 mol ratio) to give the PPh 3 ‐containing derivative [Cu{κ 3 P , Ge , P ‐GeCl(pyrmP i Pr 2 ) 2 CMe 2 }(PPh 3 )] ( 39 ; Figure ); however, under similar reaction conditions, the silver(I) and gold(I) precursors [Ag 4 (µ 3 ‐Cl) 4 (PPh 3 ) 4 ] (1:1/4 mol ratio) and [AuCl(PPh 3 )] (1:1 mol ratio) led to the PPh 3 ‐free complexes [M{κ 3 P , Ge , P ‐GeCl(pyrmP i Pr 2 ) 2 CMe 2 }] (M = Ag ( 40 ), Au ( 41 ); Figure ) . Complex 41 was more conveniently prepared using [AuCl(tht)] as gold precursor, but intractable mixtures were formed when CuCl and AgCl were used as metal precursors.…”
Section: Pgep Pincers With Bis(pyrrolyl)germylene and Dipyrromethamentioning
confidence: 99%
See 3 more Smart Citations